AGRONOMIC PERFORMANCE OF SWEET CORN (Zea mays saccharata, Sturt) IN RUMBAIDISTRICT PEKANBARU - Surtinah Surtinah (Tadulako University, 2018)
The objective of the research was to get the varieties that give the best production in RumbaiPekanbaru. The treatment design was three varieties of sweet corn, namely Sweet Bor, Sweet Lady, and Bonanza varieties. The environmental design used was a complete randomized design withsix replications. The observation parameters were cob with bractea, cob without bractea, length of cob with bractea, unsweetened length of cob, diameter of cob, and sugar content. The results obtained that Sweet Lady varieties was the best varieties.